INCIDENCE OF MALNUTRITION, ESOPHAGEAL STENOSIS AND RESPIRATORY COMPLICATIONS AMONG CHILDREN WITH REPAIRED ESOPHAGEAL ATRESIA - ASKARPOUR,Shahnam (2020)
ABSTRACT Background: Esophageal atresia is congenital anomaly with high mortality. Surgical complications and changes in nutritional status are common problems after surgical correction. Aim: To evaluate nutritional status, esophageal stenosis, and respiratory complications among children who had repaired esophageal atresia. Methods: Children aged >2 months old with repaired esophageal atresia were included in the current study. Gender, age, weight, and height were recorded for each case. Height for age and weight for age were calculated for each case. Results: According to weight for length percentile, 41.02% of the cases were underweight. Esophageal stenosis was seen in 54.76% of the obtained esophagograms. Conclusion: Underweight was present in 41.02 of the patients according to weight-for-height percentile.